Designing Superlary Game to Learn Vocabulary of Tenth Grade Students - Hesty Puspita Sari; Wahyu Dwi Lestari (EDUCATIO : Journal of Education, 2020)
The background of this research is important of vocabularyt in leaarning English. But students still difficult to adding and memorizing the vocabulary. So, to help students for learning it, the researcher develop platformer game with combination material of tenth grade students and have the result Superlary Game. To develop this media, researcher used the Sugiyono development model. This development aims to give the media to learn English vocabulary in order to increase motivate to learn English of tenth grade students of senior high school. Based on the Sugiyono model, researcher only use eight from ten steps, namely potential and problem, data collection, design product, design validation, design revision, product trial, product evaluation and final product. English Learning media produced in the form of computer-based game application used programer conctruct 2, which contains the second semester vocabulary material for class X SMA / MA students. This media completed with guiding book of how to play the game. The student’s response for this game have the result large scale trials obtaining total score are 816 from criterion score 960, percentage of students’ response are 85% this valued include in 80 < x < 100% in criterion score. So it can be concluded that the learning media developed is very good for use in learning classes in class X SMA / MA on second semester vocabulary material.